Piloting use of an out-of-pocket cost tracker among gynecologic cancer patients - Margaret I. Liang; Sarah S. Summerlin; Teresa K.L. Boitano; Christina T. Blanchard; Warner K. Huh; Smita Bhatia; Maria Pisu (Elsevier, 2022)
Objective: Our objective was to evaluate uptake and satisfaction with an out-of-pocket (OOP) cost tracker as a means for cancer patients to manage their personalized costs of care and to identify characteristics associated with usage. Methods: Within a longitudinal survey evaluating financial toxicity among gynecologic cancer patients on active systemic therapy over a 6-month period, we provided paper worksheets for participants to voluntarily track expenses. We assessed usage and satisfaction at 3 and 6 months using frequency and percentage. We used Fisher's exact test and Wilcoxon rank sum analysis to evaluate patient characteristics based upon usage. Participants were encouraged to submit their completed cost tracker worksheets. Results: Fifty-three of 121 (44%) participants reported ever using the OOP cost tracker. Most users reported it was easy to use (97%, 100%) and helpful (86%, 72%); however, fewer users rated it as useful for budgeting (42%, 26%) at 3 and 6 months, respectively. More patients who knew their insurance premium were users compared to non-users (74.4% vs. 54.4%, p = 0.04). Among thirteen users who submitted their completed cost tracker worksheets, non-medical costs (i.e., transportation) had the highest monthly out of pocket costs (mean $213, range $0-587). User feedback included suggestions to enhance the cost tracker with educational tutorials or a reminder system. Conclusions: Future studies should explore if cost tracker uptake and satisfaction are enhanced with the addition of reminders and whether usage decreases financial toxicity or increases patient self-efficacy in managing the costs of cancer care.